Three Essays in African Political Economy - (:unkn) unknown (My University, 2016)
This work is organized in three (3) chapters. the first chapter, « Electoral Institutions and Political Polarization: An Experiment on Approval Voting in Benin » coauthored with J-F Laslier, K.Van Der Straten and L. Wantchekon, focus on the institutions ‘s goal in the division of societies. The main idea is that political institutions can shape political preferences and influence the formation of groups within societies. Some system such Simple plurality and runoff majoritarian voting systems tend to force voters to “choose sides,” potentially exacerbating political, social, ethnic, or religious divisions. Voting rules that allow voters to simultaneously select several candidates should, in theory, avoid these drawbacks, and might thus lead to less polarized political outcomes. This chapter provides experimental evidence in support of this insight. Our data originates from an experiment on Approval Voting that took place during the 2011 presidential election in Benin, a democratic, multi-ethnic country in western Africa, with a political landscape characterized by a strong social and political north-south divide. In contrast to the official runoff rule used in Benin for this presidential election, we proposed Approval Voting to voters, whereby they can vote simultaneously for several candidates. We find that this electoral institution leads to an increase in the overall support for more consensual candidates. We also find that, under Approval Voting, like under Proportional Representation systems, ethnic voting does not disappear, and might even increase. The second chapter continue in the logic of voting motivation by doing some laboratory experiment about electoral clientelism. We focus on the vote buying and electoral promises. We wanted to show the impact on electoral clientelism on the election outcome in one way and in the second way, see if there is a link between modernization and clientelism. We did experiment in two different places
Keywords: African Research